PROSES PENCABUTAN PENGADUAN DAN LAPORAN DALAM TINDAK PIDANA PENGANIAYAAN DI KEPOLISIAN SEKTOR XIII KOTO KAMPAR - Muhammad Alpajri; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is a country that has a heterogeneous society, that society is diverse, ranging from ethnic, racial, cultural and religious. Of biodiversity, the often among society's conflict and friction. Conflict between these communities often lead to violence and even persecution. Act does not define what the true meaning of the "persecution". According to the jurisprudence, the sense of persecution is the act of intentionally causing discomfort, pain or injury. In the case of persecution of the country guarantee the right of any victim to obtain justice by filing a complaint or report to the appropriate authoritiesComplaints defined as an unequivocal statement (oral written or written) from a person who is entitled (pitted) submitted to authorities investigator or the investigation authorities (Indonesian National Police) about has committed a criminal offense by a person, accompanied by a request for examination to a subsequent done prosecution to the competent court. The report is the notification submitted by a person because of its rights or obligations under the Act to the authorities about have or are suspected to be the occurrence of events or criminal.Basically, the complaint can be withdrawn by the complainants or victims who are disadvantaged, while reports can not be withdrawn, although between the perpetrator and the victim has done for peace, as the complaint only to crimes that are complaint while reports for ordinary crimes. But often we encounter in society between the complaint and the report is considered the same thing, the same can be revoked when the victim and the perpetrator has made peace.Keywords:Withdrawal of complaints and reports - In the Police Sector XIII Koto Kampar -Persecution